NILAI DAN PRAKTIK ETIKA EKONOMI ISLAM DI LEMBAGA KEUANGAN SYARIAH - Maulidayati; Nor Alia (Al-Ujrah | Jurnal Ekonomi Syariah, 2025)
Over the past two decades, Islamic Financial Institutions (IFIs) in Indonesia have undergone significant growth, beginning with the establishment of Baitul Maal wat Tamwiil (BMT) in 1984. These institutions emerged in response to the public’s demand for Sharia-compliant financial services free from riba (usury). Unlike conventional financial institutions, IFIs operate in accordance with Islamic principles derived from the Qur’an and Hadith, strictly avoiding prohibited elements such as maysir (speculation), gharar (uncertainty), riba (interest), and other unlawful practices. This study adopts a literature review approach, drawing data from relevant books and scholarly journals. IFIs serve as intermediaries between those requiring funds and those with surplus capital through profit-sharing mechanisms. Moreover, they play a vital role in managing social funds—such as zakat, infaq, and sadaqah—to promote community economic welfare. The article further explores the ethical values embedded in IFI business practices and products, while emphasizing their crucial contribution to fostering economic growth and social justice in Indonesia.